Relayout Ruang Produksi untuk Meminimalkan Jarak, Waktu, dan Ongkos Material Handling di PT XYZ - Cut Aisyah Lisa Mawarni; Siti Muhimatul Khoiroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Suboptimal production facility placement is often the root of inefficiency problems, ranging from unsmooth material flow to inflated operational costs. This study aims to redesign the production line Layout of the chair division at PT XYZ using the Systematic Layout Planning (SLP) approach. Data were collected through field observations and various analytical tools such as From To Chart, Priority Scale Table, Activity Relationship Chart which were then verified through FlexSim simulation with quite significant results. The new Layout succeeded in reducing material movement distance from 1,042.51 meters to 760.64 meters (down 27.04%), speeding up movement time from 2,578.38 seconds to 1,901.60 seconds (27.04% efficiency), and reducing material handling costs from Rp2,767,220.62 to Rp2,141,482.78 or by 22.61%. These findings prove that the structured rearrangement of production facilities is able to encourage workflow efficiency and smooth production processes as a whole at PT XYZ.